Study protocol for Attachment & Child Health (ATTACHTM) program: promoting vulnerable Children's health at scale - Lubna Anis; Nicole Letourneau; Kharah M. Ross; Martha Hart; Ian Graham; Simone Lalonde; Suzanna Varro; Alanna Baldwin; Angela Soulsby; Annette Majnemer; Carlene Donnelly; Caroline Piotrowski; et al. (BMC, 2022)
Abstract Background Children's exposure to toxic stress (e.g., parental depression, violence, poverty) predicts developmental and physical health problems resulting in health care system burden. Supporting parents to develop parenting skills can buffer the effects of toxic stress, leading to healthier outcomes for those children. Parenting interventions that focus on promoting parental reflective function (RF), i.e., parents' capacity for insight into their child's and their own thoughts, feelings, and mental states, may understand help reduce societal health inequities stemming from childhood stress exposures. The Attachment and Child Health (ATTACHTM) program has been implemented and tested in seven rapid-cycling pilot studies (n = 64) and found to significantly improve parents' RF in the domains of attachment, parenting quality, immune function, and children's cognitive and motor development. The purpose of the study is to conduct an effectiveness-implementation hybrid (EIH) Type II study of ATTACHTM to assess its impacts in naturalistic, real-world settings delivered by community agencies rather than researchers under more controlled conditions. Methods The study is comprised of a quantitative pre/post-test quasi-experimental evaluation of the ATTACHTM program, and a qualitative examination of implementation feasibility using thematic analysis via Normalization Process Theory (NPT). We will work with 100 families and their children (birth to 36-months-old). Study outcomes include: the Parent Child Interaction Teaching Scale to assess parent-child interaction; the Parental Reflective Function and Reflective Function Questionnaires to assess RF; and the Ages and Stages Questionnaire - 3rd edition to examine child development, all administered pre-, post-, and 3-month-delayed post-assessment. Blood samples will be collected pre- and post- assessment to assess immune biomarkers. Further, we will conduct one-on-one interviews with study participants, health and social service providers, and administrators (total n = 60) from each collaborating agency, using NPT to explore perceptions and experiences of intervention uptake, the fidelity assessment tool and e-learning training as well as the benefits, barriers, and challenges to ATTACHTM implementation. Discussion The proposed study will assess effectiveness and implementation to help understand the delivery of ATTACHTM in community agencies. Trial registration Name of registry: https://clinicaltrials.gov/. Registration number: NCT04853888 . Date of registration: April 22, 2021.